Social anxiety symptoms and body image dissatisfaction in medical students: Prevalence and correlates - Regis, Jacqueline M. Oliveira [UNESP]; Ramos-Cerqueira, Ana Teresa A. [UNESP]; Lima, Maria Cristina P. [UNESP]; Torres, Albina Rodrigues [UNESP] (FapUNIFESP (SciELO), 2018)
Objective: Social anxiety disorder (SAD) and body image dissatisfaction (BID) are common problems among college students, but few studies focused on medical students. We aimed to estimate the prevalence, severity and correlates of SAD symptoms and BID among medical students of a Brazilian public university. Methods: A cross-sectional study with 479 students, using structured instruments: Social Phobia Inventory (SPIN), Body Shape Questionnaire (BSQ), and Beck Depression Inventory (BDI). Bivariate analyses were followed by logistic regression models to obtain independent predictors of SAD symptoms, BID and both outcomes combined. Results: Most students were single (99%) and female (58.7%). The prevalence rates of SAD symptoms (SPIN ≥ 19) and BID (BSQ ≥ 81) were 36.3% and 34.7%, respectively. Depressive symptoms (BDI ≥ 19) occurred in 8.8% of the sample. SAD symptoms were independently associated with: BID, thoughts of abandoning the course, difficulty making friends, depressive symptoms, and mental health treatment prior to university. Besides SAD symptoms, BID was associated with female sex, difficulty making friends, depressive symptoms, and body mass index (BMI). Seventy-eight students (16.3%) presented SAD symptoms and BID, which was associated with female sex, difficulty making friends, dissatisfaction with the course, depressive symptoms and BMI. Conclusion: SAD symptoms and BID are common and related problems that should be screened for among medical students. The identification of specific correlates could contribute to the elaboration of preventive measures, minimizing the distress and negative impact of these mental health problems on relationships and academic performance.
Sintomas de ansiedade social e insatisfação com a imagem corporal em estudantes de medicina: Prevalência e correlatos
Keywords: Body image dissatisfaction; Depressive symptoms; Medical students; Social anxiety disorder; Social phobia